FAMILY CLEAN AND HEALTHY LIVING BEHAVIOR AND ITS DETERMINANT FACTORS IN THE VILLAGE OF LABUNIA, REGENCY OF MUNA, SOUTHEAST SULAWESI PROVINCE OF INDONESIA - Jayadipraja, Erwin Azizi; Prasetya, Fikki; Azlimin, Azlimin; Mando, Wa Ode Sitti Yuliana (YCAB Publisher & IAKMI SULTRA, 2018)
Background: The campaign of a clean and healthy living behavior (PHBS) in Indonesia continues to be conducted to improve the public health. During five years of monitoring (2012-2015) the highest PHBS rate in Southeast Sulawesi reached only 49.75% in 2013. While PHBS data in Labunia Village of Muna Regency reached only 7.71% in 2015.Objective: This study aims to determine the factors associated with the clean and healthy living behavior (PHBS) of family in the Village of Labunia, regency of Muna, Southeast Sulawesi province of Indonesia.Methods: This was observational analytics with cross-sectional design study. The populations of the study were all household heads who lived in Labunia Village which were 293 households and 75 samples were selected using simple random sampling. Data were analyzed using chi-square test.Result: Of the total of respondents, 36% of family implemented PHBS and 64% of them did not implement PHBS. There were 16% of respondents had good knowledge, 48% of good attitude, and 45.3% of good actions in PHBS. Chi square test results obtained a significant correlation between knowledge, attitude and action in PHBS with p = 0.00 (<0.05).Conclusion: There was a moderate correlation between knowledge, attitudes and actions towards the family clean and healthy living behavior in the Village of Labunia, regency of Muna, Southeast Sulawesi province of Indonesia.